Phosphatidylinositol 4-kinases: Function, structure, and inhibition - Boura, Evzen; Nencka, Radim (Experimental cell research, 2015)
The phosphatidylinositol 4-kinases (PI4Ks) synthesize phosphatidylinositol 4-phosphate (PI4P), a key member of the phosphoinositide family. PI4P defines the membranes of Golgi and trans-Golgi network (TGN) and regulates trafficking to and from the Golgi. Humans have two type II PI4Ks (α and β) and two type III enzymes (α and β). Recently, the crystal structures were solved for both type II and type III kinase revealing atomic details of their function. Importantly, the type III PI4Ks are hijacked by +RNA viruses to create so-called membranous web, an extensively phosphorylated and modified membrane system dedicated to their replication. Therefore, selective and potent inhibitors of PI4Ks have been developed as potential antiviral agents. Here we focus on the structure and function of PI4Ks and their potential in human medicine.
Keywords: Antiviral Agents; buněčná membrána; trans-Golgi Network; transport proteinů; Animals; Cell Membrane; Humans; 1-Phosphatidylinositol 4-Kinase; 1-fosfatidylinositol-4-kinasa; lidé; antivirové látky; zvířata; trans-Golgiho síť; Protein Transport